2021
DOI: 10.21203/rs.3.rs-403341/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Acute Sprint Interval Training on Cognitive Performance of Healthy Younger Adults

Abstract: Considerable evidence has been accumulated showing that an acute bout of physical exercise can improve cognitive performance but the optimal exercise characteristics (e.g., exercise type and intensity) remain elusive. In this regard, there is a gap in the literature to which extent Sprint Interval Training (SIT) can enhance cognitive performance. Thus, this study aimed to investigate the effect of SIT on cognitive performance. We assessed in healthy younger adults (n = 19; 20.0 to 28.0 years old), the attentio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In contrast, blood lactate substantially increases during/after high-intensity exercise, and it is taken up by the brain Gonzalez-Alonso et al, 2004;Quistorff et al, 2008;Siebenmann et al, 2021). Several studies suggested that blood lactate would provide energy that contributes to improvements in cognitive performance following HIIE (Tsukamoto et al, 2016;Hashimoto et al, 2018;Herold et al, 2022). In particular, Hashimoto et al (2018) directly measured lactate uptake in the brain after HIIE and suggested that lactate production in extra-cerebral tissues supports brain function.…”
Section: Cerebral Metabolismmentioning
confidence: 99%
“…In contrast, blood lactate substantially increases during/after high-intensity exercise, and it is taken up by the brain Gonzalez-Alonso et al, 2004;Quistorff et al, 2008;Siebenmann et al, 2021). Several studies suggested that blood lactate would provide energy that contributes to improvements in cognitive performance following HIIE (Tsukamoto et al, 2016;Hashimoto et al, 2018;Herold et al, 2022). In particular, Hashimoto et al (2018) directly measured lactate uptake in the brain after HIIE and suggested that lactate production in extra-cerebral tissues supports brain function.…”
Section: Cerebral Metabolismmentioning
confidence: 99%